2005
DOI: 10.1117/12.570913
|View full text |Cite
|
Sign up to set email alerts
|

Design and analysis of bow tie aperture with strong near-field enhancement effect

Abstract: In this paper the near-field distributions of bow-tie apertures in visible range are characterized by the method of 3D finite-difference time-domain (FDTD). The numerical simulation results reveal theoretically the relation of field enhancement effect of bow-tie aperture and its several parameters including tip angle, aperture size and film thickness. For the bow-tie aperture with a certain tip angle, the metallic film's thickness can be firstly determined at its resonant peak, and then the aperture size can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Numerous studies have simulated the far-field and near-field pattern of electromagnetic wave penetrating through the bowtie shaped aperture, the excitation radiation intensity shows great dependence on gap size, tip angles and beam size. [7][8][9] Other research groups also provided experimental results which demonstrated polarization characteristic 10 and plasmonic resonance involved in this kind of structure. 11 It is well understood that one can easily choose the suitable geometrical parameters of bowtieshaped aperture to meet the requirements.…”
mentioning
confidence: 91%
“…Numerous studies have simulated the far-field and near-field pattern of electromagnetic wave penetrating through the bowtie shaped aperture, the excitation radiation intensity shows great dependence on gap size, tip angles and beam size. [7][8][9] Other research groups also provided experimental results which demonstrated polarization characteristic 10 and plasmonic resonance involved in this kind of structure. 11 It is well understood that one can easily choose the suitable geometrical parameters of bowtieshaped aperture to meet the requirements.…”
mentioning
confidence: 91%